The effect of aeration and non-aeration time on simultaneous organic, nitrogen and phosphorus removal using an intermittent aeration membrane bioreactor - Ujang, Zaini; Salim, M. R.; Khor, S. L. (Elsevier Science B.V., Amsterdam, 2002)
A laboratory-scale membrane bioreactor (MBR) was fed with synthetic wastewater to investigate the possibility of simultaneous removal of organic, nitrogen and phosphorus by intermittent aeration. The MBR consists of two compartments using a microfiltration membrane with 0.2 µm pore size and a surface area of 0.35 m2. Hydraulic retention time was set at 24 hours and solid retention time 25 days. MLSS concentration in the reactor was in the range of 2,500–3,800 mg/L. The MLSS internal recycling ratio was maintained at 100% influent flow rate. Intermittent aeration was applied in this study to provide an aerobic–anaerobic cycle. Three stages of operations were conducted to investigate the effect of aeration and non-aeration on simultaneous organic and nutrient removal. In Stage 1, time cycles of aeration and nonaeration were set at 90/150 min and 150/90 min in the first and second compartment, the removal efficiency was 97%, 94% and 70% for COD, nitrogen and phosphorus respectively. In Stage 2, time cycles of aeration and non-aeration were set at 60/120 min and 120/60 min in the first and second compartment, the removal efficiency was 97%, 96% and 71% for COD, nitrogen and phosphorus respectively. In Stage 3, time cycles of aeration and non-aeration were set at 120/120 min and 120/120 min in compartment 1 and 2, the removal efficiency was 98%, 96% and 78% for COD, nitrogen and phosphorus respectively. Results show that longer non-aeration time in the second compartment provided better performances of biological phosphorus removal